(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Background: Fatal road traffic accidents (RTA) are a major cause of concern all over the world. The outcome of injuries sustained in an RTA depends on various factors including but not limited to: the location of the event, type of vehicle involved, nature of the roads, the time of accident, etc. Materials and Methods: The present study included all the fatal Road Traffic Accident cases, which had been brought to mortuary of Maharaja Agrasen Medical College during the period 1/02/2021 to 31/01/2022 with a sample size of 81 cases. Before and during conduction of postmortem examination, data was collected by using pre-designed semi structured proforma by the investigator himself. The data thus obtained was subjected to further suitable statistical analysis. Results: Among 81 cases, maximum deaths occurred in age group of 21-30 years and 82.7% were males. Most of the study participants (34.6%) were doing labour work. Approximately, 40% participants were brought dead in hospital. Among total victims, 46% were drivers, 23.5% were passengers, and 30.9% were pedestrians. About 55% of all deaths occurred in occupants of two wheelers. More than 85% victims experienced injuries on head. Fracture was the most common (85.2%) type of injury followed by abrasions (82.7%), lacerations (67.9%) and contusions (50.6%). The most commonly damaged internal organ was brain ( 75%). The most common cause of death (48.2%) was head injury followed by complications due to head injury (9.9%), haemorrhage and shock due to multiple injuries (24.7%) and traumatic shock due to multiple injuries (12.4%). Conclusion: It may be concluded that there is urgent need to address the epidemic of RTA on the roads. Road traffic deaths are to a great extent preventable.